2019
DOI: 10.36932/jpcam.v2i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Uji Aktifitas Antikoagulan Ekstrak Alkaloid Total Daun Alpukat (Persea americana Mill) Secara In Vitro

Abstract: Sistem hemostasis yang tidak seimbang akan menyebabkan kelainan patologis. Kelainan patologis yang dapat terjadi yaitu perdarahan spontan karena darah tidak dapat membeku, atau terbentuknya trombus jika koagulasi berlebihan. Salah satu obat yang digunakan untuk mengatasi kelainan tersebut adalah penggunaan obat antikoagulan. Alkaloid diketahui memiliki aktivitasabtikoagulan dengan menghambat jalur koagulasi secara ekstrinsik dan intrinsik melalui penghambatan produksi Fxa, trombin dan menghambat TNF-λ yang dii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on the test results showed that the total alkaloids extracted from the leaves of P. americana Mill. can prolong the coagulation time significantly (P < 0.05) concerning the inhibition of coagulation (15) . Alkaloid compounds work by inhibiting or prolonging the activity of thrombin and factor Xa and inhibiting the polymerization of fibrin into thrombin, alkaloids also prolong the CT process in the blood.…”
Section: Ersea Americana Millmentioning
confidence: 94%
“…Based on the test results showed that the total alkaloids extracted from the leaves of P. americana Mill. can prolong the coagulation time significantly (P < 0.05) concerning the inhibition of coagulation (15) . Alkaloid compounds work by inhibiting or prolonging the activity of thrombin and factor Xa and inhibiting the polymerization of fibrin into thrombin, alkaloids also prolong the CT process in the blood.…”
Section: Ersea Americana Millmentioning
confidence: 94%